Humphrey's creepy-crawly camping adventure - Birney, Betty G. (Birney, Betty G. Humphrey's tiny tales, 2015)
"Humphrey goes on a backyard camping adventure with his classmates and meets all kinds of outdoor creatures--even some scary ones"--